Metabolic Phenotype and Microbiome of Infants Fed Formula Containing Lactobacillus paracasei Strain F-19 - Lee, Hanna; Li, Zailing; Christensen, Britt; Peng, Yongmei; Li, Xiaonan; Hernell, Olle; Lönnerdal, Bo; Slupsky, Carolyn M. (Frontiers in Pediatrics, 2022)
Early childhood nutrition drives the development of the gut microbiota. In contrast to breastfeeding, feeding infant formula has been shown to impact both the gut microbiota and the serum metabolome toward a more unfavorable state. It is thought that probiotics may alter the gut microbiota and hence create a more favorable metabolic outcome. To investigate the impact of supplementation with Lactobacillus paracasei spp. paracasei strain F-19 on the intestinal microbiota and the serum metabolome, infants were fed a formula containing L. paracasei F19 (F19) and compared to a cohort of infants fed the same standard formula without the probiotic (SF) and a breast-fed reference group (BF). The microbiome, as well as serum metabolome, were compared amongst groups. Consumption of L. paracasei F19 resulted in lower community diversity of the gut microbiome relative to the SF group that made it more similar to the BF group at the end of the intervention (4 months). It also significantly increased lactobacilli and tended to increase bifidobacteria, also making it more similar to the BF group. The dominant genus in the microbiome of all infants was Bifidobacterium throughout the intervention, which was maintained at 12 months. Although the serum metabolome of the F19 group was more similar to the group receiving the SF than the BF group, increases in serum TCA cycle intermediates and decreases in several amino acids in the metabolome of the F19 group were observed, which resulted in a metabolome that trended toward the BF group. Overall, L. paracasei F19 supplementation did not override the impact of formula-feeding but did impact the microbiome and the serum metabolome in a way that may mitigate some unfavorable metabolic impacts of formula-feeding.